Analisis Pengaruh Jumlah Pinjaman, Jumlah Simpanan Dan Jumlah Anggota Koperasi Terhadap Sisa Hasil Usaha (Studi Kasus Pada Koperasi Abdi Kasih Tumpang Periode 2016-2020) - Galuh Budi Astuti; Nia Purwati (Universitas Katolik Widya Karya Malang, 2022)
The purpose of this study was to analyze the effect simultaneously, partially, and look for the variable that has the most dominant influence between the number of loans, the number of deposits and the number of members on the remaining results of operations at the Abdi Kasih Tumpang Cooperative for the 2016-2020 period. The type of research used is explanatory research. The type of data used is quantitative data. Source in this study using primary data sources. This data collection method is observation and interviews. The data analysis technique used is descriptive statistical analysis, classical assumption test, multiple linear analysis test and dominant test. Simultaneously the number of loans, the number of savings and the number of members affect the remaining operating results. Partially the number of loans, the number of savings and the number of members does not affect the remaining operating results. There is no variable that has the most dominant influence in this study, because partially, the independent variables have no effect on the dependent variable.